1996
DOI: 10.1126/science.272.5261.542
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of NF-κB by Nerve Growth Factor Through the Neurotrophin Receptor p75

Abstract: Nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT-3) selectively bind to distinct members of the Trk family of tyrosine kinase receptors, but all three bind with similar affinities to the neurotrophin receptor p75 (p75NTR). The biological significance of neurotrophin binding to p75NTR in cells that also express Trk receptors has been difficult to ascertain. In the absence of TrkA, NGF binding to p75NGR activated the transcription factor nuclear factor kappa B (NF-kappa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
424
2
7

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(449 citation statements)
references
References 35 publications
16
424
2
7
Order By: Relevance
“…p75 NTR has been shown to enhance NGF binding and signaling through TrkA (51)(52)(53)(54). p75 NTR also initiates signal transduction separately from TrkA (55)(56)(57). There is increasing evidence that the signals generated by p75 NTR promote programmed cell death (58)(59)(60)(61) rather than prevent it, as does TrkA (62).…”
Section: Resultsmentioning
confidence: 99%
“…p75 NTR has been shown to enhance NGF binding and signaling through TrkA (51)(52)(53)(54). p75 NTR also initiates signal transduction separately from TrkA (55)(56)(57). There is increasing evidence that the signals generated by p75 NTR promote programmed cell death (58)(59)(60)(61) rather than prevent it, as does TrkA (62).…”
Section: Resultsmentioning
confidence: 99%
“…A growing list of signals that can activate NF-kB in neurons includes tumor necrosis factor-a (TNF), 9 the excitatory neurotransmitter glutamate, 3 nerve growth factor (NGF), 10,11 activity-dependent neurotrophic factor (ADNF), 12 a secreted form of amyloid precursor protein 13 and cell adhesion molecules. 14 These molecules can activate NF-kB through coupling to kinase cascades including calcium/calmodulindependent kinase II, 15 Akt 16,17 and protein kinase C 18 ( Figure 2).…”
Section: The Basics Activation Of Nf-jb In Neuronsmentioning
confidence: 99%
“…Separate activation of either the p75 NTR or trkA is sufficient to lead to NF-kB activation. 10,31 However, interactions in the signaling pathways downstream of either trkA or p75 NTR are likely to have potential impacts on NF-kBdependent regulation of gene expression. In studies using chimeric receptors to isolate the signaling pathways in a neuronal cell line (PC12), Foehr et al found that the p75 NTR activated the p65, p50 and p52 subunits of NF-kB, while trkA activated only p50 and p65.…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…Indeed, it has been reported that NGF binding to p75 NTR stimulate glycosyl-phosphatidylinositol hydrolysis in cochleovestibular ganglia cells (Represa et al, 1991) and induces di erentiation, through the sphingomyelin pathway, in glioma cells that lack TrkA (Dobrowsky et al, 1994). Furthermore, activation of the transcription factor NF-kB by NGF, but not BDNF or NT-3 through p75 NTR has been reported in Schwann cells (Carter et al, 1996). These ®ndings clearly demonstrate the existence of di erent signal transduction pathways speci®cally coupled to p75 NTR , independent of TrkA.…”
Section: Bep75bmentioning
confidence: 99%